Arbuscular mycorrhizal fungal contribution towards plant resilience to drought conditions - Das, Subhadeep; Sarkar, Soumyadev (Frontiers in Fungal Biology, 2024)
Climate changes cause altering rainfall patterns resulting in an increase in drought occurrences globally. These events are disrupting plants and agricultural productivity. To evade droughts, plants try to adapt and modify in the best capacities possible. The plants have adapted by structurally modifying roots, stems, and leaves, as well as modifying functions. Lately, the association of microbial communities with plants has also been proven to be an important factor in aiding resilience. The fungal representatives of the microbial community also help safeguard the plants against drought. We discuss how these fungi associate with plants and contribute to evading drought stress. We specifically focus on Arbuscular mycorrhizal fungi (AMF) mediated mechanisms involving antioxidant defenses, phytohormone mediations, osmotic adjustments, proline expressions, fungal water absorption and transport, morphological modifications, and photosynthesis. We believe understanding the mechanisms would help us to optimize the use of fungi in agricultural practices. That way we could better prepare the plants for the anticipated future drought events.